STEM-based worksheet on digestive system material to improve students’ creative thinking skills - Khairuna Khairuna (Jurnal Biolokus, 2023)
One of the problems that often occur in the learning process is the low level of student's creative thinking which can be seen from four aspects, namely fluency, flexibility, originality, and elaboration. Efforts that can be made to improve students' creative thinking abilities include developing learning tools based on the STEM learning approach. This study aims to produce biology worksheet based on STEM approaches in digestive system material that is valid, practical, and effective in improving students' creative thinking skills. The type of research carried out is research and development by using the 4D model (Define, Design, Develop and Disseminate).  The instrument used was validation sheets, questionnaire, and test. In this study, the average score of students' creative thinking ability was 85.30 with a completeness percentage of 87.5%. Based on the results obtained, it can be concluded that the STEM-based worksheet in digestive system material is declared valid and feasible for use and can improve students' creative thinking.